Intravitreal Triamcinolone Reinjection for Refractory Diabetic Macular Edema - Ramezani, Alireza (The Korean Ophthalmological Society, 2006)
PURPOSE: To evaluate the effect of intravitreal triamcinolone acetonide (IVT) reinjection on clinical and optical coherence tomographic features in refractory diabetic macular edema. METHODS: In a prospective interventional case series, all IVT treated patients enrolled in a previous clinical trial were recalled to have a new ophthalmologic examination and optical coherence tomography (OCT) performed. Eyes found suitable for reinjection received 4 mg IVT. Complete clinical examination and OCT were repeated at 2 and 4 months post-injection. The changes were statistically analyzed using a paired t test and were compared to the results of the first injections. RESULTS: Of all returning patients, 12 cases with complete records were considered candidates for reinjection. Visual acuity (VA) changes were not significant after the first and second interventions, although there was a relative improvement (0.14 logMAR) 2 months after the first injection. Reductions of central macular thickness (CMT) were 43±69 µm, and 40±69 µm after the first injection and 27±48 µm, 49±58 µm after the reinjection at 2 & 4 months, respectively. None of the mentioned changes was significant. After the second injection, however, intraocular pressure was elevated at both 2 & 4 months (3.6 & 2.4 mmHg respectively, P<0.05). Two months after the first administration, intraocular pressure was found to be raised significantly (5.58 mmHg, P=0.001). CONCLUSIONS: The transient beneficial effects of IVT on diabetic macular edema are not repeated with second injections. However, IVT-related ocular hypertension is more persistent after reinjection.